Religion and abortion: the role of politician identity - Bhalotra, Sonia (Discussion paper series, 2018)
Leveraging close elections to generate quasi-random variation in the religious identity of state legislators in India, we find lower rates of female foeticide in districts with Muslim legislators, which we argue reflects a greater (religious) aversion to abortion among Muslims. These districts exhibit increases in fertility that offset the decrease in girl abortion. We find no evidence of greater postnatal neglect of girls once more girls are born. Our findings show that politician preferences over abortion influence abortion-related outcomes, most likely through greater enforcement of laws against sex determination.